Risky Returns: The Implications of Financialization in the Food System - Clapp, Jennifer; Isakson, S. Ryan (Development and Change, 2018)
This article examines the rise of financialization in the agrifood sector and maps out both the way it has unfolded as well as its implications. The article argues that financialization has opened up new arenas for capital accumulation in the agrifood sector; reshaped the agrifood firms in ways that respond to demands of shareholders; and transformed everyday practices of food and social provisioning. The authors make the case that these three broad processes, while each important in their own right, are interconnected and mutually reinforcing. The article also argues that the complex iteration of financialization in the agrifood sector carries three important implications for the long-term social and ecological sustainability of food and agricultural provisioning: it exacerbates the existing imbalances of power and wealth in the food system; it increases economic and ecological vulnerabilities within agrifood systems; and it has evolved in ways that impede and dampen collective demands for change and resistance. Taken together, these wider implications of financialization in the agrifood sector present a direct challenge to the ability of food systems to provide livelihoods and food security over the long term.